Inflammation-related cytokine gene polymorphisms in Behçet’s disease - Al-Okaily F; Arfin M; Al-Rashidi S; Al-Balawi M; Al-Asmari A (Dove Medical Press, 2015)
Fahda Al-Okaily,1 Misbahul Arfin,2 Seham Al-Rashidi,1 Maysoon Al-Balawi,1 Abdulrahman Al-Asmari2 1Department of Rheumatology, 2Division of Molecular Biology and Genetics, Research Center, Prince Sultan Military Medical City, Riyadh, Saudi Arabia Abstract: Behçet’s disease (BD) is a complex, multisystemic inflammatory disorder of unclear etiology. Single nucleotide polymorphisms in tumor necrosis factor (TNF) and interleukin (IL)-10 genes have been implicated in susceptibility to BD with inconsistent results in several ethnic populations. The aim of this case-control study was to evaluate the association of TNF-α (−308G/A), TNF-β (+252A/G), and IL-10 (−1082G/A, −819C/T, and −592 C/A) polymorphisms with susceptibility of BD in Saudi patients. Molecular genotyping of TNF-α, TNF-β, and IL-10 gene polymorphisms was performed to analyze the alleles and genotypes distribution in 272 Saudi subjects, including BD patients (61) and healthy controls (211). The frequencies of allele A and genotype GA of TNF-α (−308G/A) were significantly higher, whereas those of allele G and genotypes GG were significantly lower in BD patients than controls, indicating that A allele and GA genotype are susceptible, while G allele and GG genotype may be refractory to BD. The distribution of frequencies of alleles and genotype of TNF-β (+252A/G) promoter polymorphism was not significantly different between BD patients and healthy controls. Genotypes 1082GG, −819TT, and 592AA of IL-10 polymorphisms are significantly associated with susceptibility risk of BD, while genotypes 1082AA, 1082GA, 819CC, 819CT, 592CC, and 592CA are resistant to BD. This study indicates that TNF-α (−308G/A) and IL-10 (−1082G/A, −819C/T, and −592C/A) polymorphisms are associated with risk of BD susceptibility in Saudi patients. However, larger scale studies in Saudi population as well as in other ethnicities are needed to confirm this association. Keywords: tumor necrosis factor, interleukin-10, polymorphism, Saudis, Behçet's disease